Elastic reversible valves on centrifugal microfluidic platforms - Aeinehvand, Mohammad Mahdi; Weber, Laura; Jiménez, Martín; Palermo, Andrea; Bauer, Maria; Loeffler, Felix F.; Ibrahim, Fatimah; Breitling, Frank; Korvink, Jan; Madou, Marc; Mager, Dario; Martínez-Chapa, Sergio O. (Royal Society of Chemistry, 2019)
Reversible valves on centrifugal microfluidic platforms facilitate the automation of bioanalytical assays, especially of those requiring a series of steps (such as incubation) in a single reaction chamber. In this study, we present fixed elastic reversible (FER) valves and tunable elastic reversible (TER) valves that are easy to fabricate, implement and control. In the FER valve the compression of an elastic barrier/patch against a microchamber's outlet prevents the release of liquid. The valve sealing pressure was determined by adjusting the engraving depth of the valve-seat at which the elastic patch was located, this allows to set the sealing pressure during disc fabrication. In the TER valve, the patch compression value and sealing pressure is controlled by the penetration depth of a plastic screw into the valve-seat. The ER valves prevent liquid flow until the centrifugal force overcomes their sealing pressure. Moreover, at a constant spin speed, turning the screw of a TER valve reduces its sealing pressure and opens the valve. Therefore, the TER valve allows for controlling of the liquid transfer volume at various spin speeds. The FER and TER valves' behavior is mathematically described and equations for the prediction of their operation under centrifugal forces are provided. As a point-of-care (POC) application of ER valves, we have developed a microfluidic disc with a series of TER valves and peptide microarrays for automated multiplexed detection of five different proteins from a single serum sample. © The Royal Society of Chemistry.